PENGARUH RAWAT LUKA DENGAN TEKNIK MODERN DRESSING PADA PASIEN ULKUS DIABETIC - Purnawan Utama AS; Hariawan Junardi (Akademi Kebidanan Harapan Bunda Bima, 2026)
Diabetic ulcers are wounds that occur in people with Diabetes Mellitus due to complications of microangiopathy and macroangiopathy. Diabetic foot ulcers are damage that occurs partially (partial thickness) or completely (full thickness) in the skin area that extends to the subcutaneous tissue, tendons, muscles, bones or joints. One effort to overcome the problem of diabetic ulcers is by performing wound care. Wound care is the act of treating wounds by creating moist conditions in the wound so that it can help the process of epithelialization and wound healing. Wound cleaning treatment can be done by using physiological fluids such as normal saline (NaCl 0.9%) to maintain wound moisture and keep granulation dry. The purpose of this case report is to determine the effect of wound care in treating diabetic ulcers. The method used in this study is a case study (case report). The sample in this case report is a patient with the main complaint of diabetic ulcers on the lower extremities. The data collection method used in this study was carried out through interviews, observations and physical examinations. The conclusion of this case report is that there is an influence of wound care using the modern dressing method on the ulcer wound healing process.